Attracting private solutions and participation in the power sector in Sub-Saharan Africa - Probst, Benedict,Holcroft, Richard,Huenteler, Joern,Balabanyan, Ani,Tipping, Andrew,Robinson, Peter (World Bank Group, Energy and Extractives Global Practice, 2020)
This paper develops a classification of investor risks and surveys 51 private investors and financiers in the power sector in Sub-Saharan Africa. The paper aims for a better understanding of what can be done to attract private solutions to fill the investment gap. It finds that the average investor assigns more weight to power sector policy and regulatory framework risks than to the wider sector and country context risks. And, despite many challenges, investors perceive three segments as ready for private solutions in Sub-Saharan Africa: power generation, off-grid electrification, and mini-grids. Investors see lower readiness in distribution, transmission, and retail. The paper finds that the average investor is forward-looking, as neither the track record of the power sector nor the firm's personal track record is as important as the growth potential in the market. The paper uses the findings to reality-check data-based measures of regulatory readiness, namely the Regulatory Indicators for Sustainable Energy and Power Sector Reform Index and analyzes which elements correlate best with investor sentiment to optimize and streamline these indexes accordingly. The results provide important lessons for governments and development partners to devise appropriate de-risking instruments tailored to the risks that matter most to investors
10.1596/1813-9450-9299
Keywords: Graue Literatur; Private investment; investment risks; electricity; financial viability; developing countries; emerging markets